Improving Trust in News: Audience Solutions. (26th November 2021) - Fisher, Caroline; Flew, Terry; Park, Sora; Lee, Jee Young; Dulleck, Uwe
ABSTRACT: As the news media continue to search for sustainable business models in response to digitisation, concern about low levels of trust in news has been rising. Trust in news brands is seen as an essential pre-requisite for their economic survival. While there is extant research on the crisis of trust in news, less attention has been paid to identifying possible solutions from the perspective of the audience. Based on a survey of 1619 Australian news consumers, this paper helps address this gap. Informed by existing research, participants were asked about a range of possible factors influencing their perceptions of trust in news. Participants expressed strongest support for reducing bias and opinion from journalists in stories, making reporters declare all conflicts of interest, and boosting the amount of in-depth reporting. Increasing journalists' activity on social media and employing more reporters, were less supported remedies, particularly among those who tend to have low trust in news. Those who have higher trust in news are more supportive of options to boost their trust further, whereas those with low trust innews are less enthusiastic. These findings highlight the challenge for news organisations of improving perceptions of trust among those who are already sceptical about the news.